The role of the alternative pathway of the complement system in the development of dense deposit disease - Abeleda, Maria Asuncion Abrera; Smith, Richard H.; University of Iowa. (Ann Arbor, MI ProQuest Dissertations & Theses Global, 2010)
"Dense Deposit Disease (DDD) causes chronic renal dysfunction which progresses to end-stage renal disease in about half of patients within 10 years of diagnosis. Deficiency of and mutations in complement Factor H (CFH) are associated with the development of DDD, suggesting that dysregulation of the alternative pathway (AP) of the complement cascade is important in disease pathophysiology. Patients with DDD were studied to determine whether specific allele variants of the genes of the alternative pathway of the complement system segregate preferentially with the DDD. Coding and intronic regions of genes of the complement system in DDD cases and controls were screened for variants using PCR, restriction digest and bidirectional sequencing. We were able to identify novel mutations, allele variants and haplotypes in several genes of the complement system, which are associated with the DDD phenotype. Possible gene-gene interactions were determined using computational analyses. A strong synergistic interaction between polymorphisms in Complement Factor H and C3 was observed. To ascertain if the associated allele variants have a functional impact in complement activity, serum samples from normal controls were genotyped for variants in CFH and C3 and AP complement activity was measured. We found a significant association between CFH and C3 variants and AP complement activity. Lastly, we generated mutant mice deficient in CFH and Factor D (CFD). CFH deficient mice develop renal pathology similar to DDD. Renal function and complement activity in mice deficient in both CFH and CFD were compared to CFH deficient and CFD deficient mice. The absence of Factor D inhibits complement activation in CFH-deficient mice. In aggregate, our data show that: (1) DDD is a complex genetic disease; (2) mutations and allele variants of genes of the AP complement system contribute to the level of complement activity and the pathogenesis of DDD; (3) the deletion of CFD rescues the disease phenotype in a murine model of DDD. These findings should facilitate the diagnosis of DDD and provide targets that can be explored as potential therapies in affected patients." -- Abstract
Dissertation (PhD in Genetics)--University of Alberta, 2010.
Keywords: Electronic books; Kidneys -- Diseases -- Genetic aspects; Alternative pathway -- Animal models -- Association studies -- Complement activity -- Complement system -- Dense deposit disease